WORD FORMATION PROCESSES IN THE NAMES OF DIGITAL HEALTH PLATFORMS - Juwita, Imas Nita; Aulia, Hernita Ratna (Faculty of Letters Universitas Balikpapan, 2025)
This research is conducted to examine the word formation processes contained in the naming of digital health platforms in Indonesia This research would mainly focus on analyzing how the patterns of language, culture and region influence the trends of name creation in the global digital health sector. This research uses qualitative research in a morphosemantic approach. From the result analysis, some types of word-formation processes include compounding, blending, and clipping,to identify the strategies behind these naming conventions.The findings reveal that digital health platforms in Indonesia often combine local Indonesian elements, such as